Applying Of Fair Value In Algerian Banks According To Financial Accounting System - Ghrissi, Jihad; Boumedya, Youssef (جامعة الوادي - University of Eloued, 2017)
This study aimed to introduce fair value concept as a measurement basis, and how Algerian financial system can consider it, however fair value concept proposed as a solution to criticisms that faced accounting measurement because of using different accounting bases, especially historical cost . Also, researchers discussed in the study the importance of accounting measurement, and efforts of international professional organizations and standards body setters especially International Accounting Standards Board(IASB) and American Financial Accounting Standards Board (FASB), to the necessity of proposing accounting measurement basis finalize the criticisms that directed to accounting profession relate to measurement, both boards agreed to consider fair value as the relevant accounting measurement , in spite of criticisms of it. Finally, researchers discussed fair value in Algerian financial accounting system and related legislations, also the importance of applying fair value by Algerian banks as they represent the main core in Algerian economy, and as a part of international banking sector. Researchers concluded to necessity of considering the latest amendments relate to fair value in international accounting standards by Algerian financial accounting system, and recommend to include the Algerian financial accounting system to all updating relates to fair value in order not to isolate Algerian economy from the global economy that does its best efforts to conceptualize fair value as an measurement basis that get rid of all criticisms of accounting measurement.
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: Fair value ; Algerian financial accounting system; accounting measurement.